Surgical treatment of advanced oropharyngeal cancer with preservation of the larynx - Balatoni, Zsuzsa (Radiology and oncology (Ljubljana), 1999)
Background and methods. This retrospective study evaluates the oncological andfunctional results obtained in 61 patients with advanced oropharyngeal cancer who underwent extended tumor resection as a primary procedure or as a salvage surgery form. Results. Although the oropharyngeal cancers involved thebase of the tongue, or some of them extended to the lateral hypopharyngeal wall, the surgery was performed without total laryngectomy. The tumor extendedto the vallecula and/or to the pharyngoepiglottic fold in five cases, which required supraglottic laryngectomy. The closure following the extended resection of the tumor was made with flap reconstruction in all patients. The preferred method was employing the pectoralis major myocutaneus flap. The survival rates were 75%, at 1 year and 31 %, at 2 years and 25% from 2 to 5 years with recurrence of the disease. In one patient, the nasogastric tube could not have been removed, and another patient could be decannulated only after postoperative radiation because of the persistent oedema. Conclusions. Asatisfactory functional result was obtained in this series. In most of our patients, good functioning of larynx as well as voice preservation were secured.
Keywords: Laryngectomy; Larynx; Methods; Neoplasm staging; Oropharyngeal neoplasms; Radical neck dissection; Retrospective studies; Surgery; Surgical flaps; Treatment outcome